PENGARUH POSITIVE AFFIRMATION TERHADAP MASALAH MAKAN PADA ANAK - Esty Puji Rahayu; Nanik Handayani; Lailatul Khusnul Rizki (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Effect of Positive Affirmation on Eating Problems on ChildrenBackground: growth disorders cannot be separated from how a mother gives food to her toddler. Feeding children is considered a natural process, however, 50-60% of parents report that their child has feeding problems. Objectives: :  to analyze the positive effect of affirmation on children's eating problems (Picky and small eaters). Methods: this study used a quasi-experimental study with one group pre-test-post-test. The independent variable is a positive affirmation, while the dependent variable is eating problems in toddlers including small eaters and picky eaters. This research was conducted at Raudlatul Jannah Preschool, Sidoarjo and the respondents were the guardians of the students at the school. The instrument uses an affirmation flashcard and a questionnaire. The population is the guardians of the kindergarten class as many as 46 people. With simple random sampling obtained a sample of 41 respondents. Results: based on the results of data analysis with the Paired T Test on the picky eater variable before and after being given a positive affirmation using flashcard affirmation media, it shows that p = 0.008 (p <0.05) which means that there is a significant effect between positive affirmations on picky eaters. Likewise, the small eater variable shows the result that p = 0.017 (p <0.05), which means that there is a significant effect between positive affirmations and small eaters in children. Conclusion: there is a positive affirmation effect on children's eating problems (picky eaters and small eaters).